2021
DOI: 10.1088/1755-1315/653/1/012125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic fertilizer and application of charcoal on quality of potato tuber variety atlantic

Abstract: The widely cultivated tuber in Indonesia is Granola. The Granola tuber is appropriate for table potato and not for processing one. The cultivation of potato cultivar Atlantic for processed potato should be increased. This research aimed to examine the quality of potato cultivar Atlantic with organic farming and compare their properties with a conventional system. Potato tuber cultivar Atlantic was cultivated with conventional and organic fertilizer. Fertilization was performed following the practices of the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…The result was in agreement with the finding of Wibowo et al, (2021) they mentioned that the difference in tuber color is caused by differences in the carotene pigment content in each variety.…”
Section: Both Of Inside and Outside Color Index Potato Tuberssupporting
confidence: 92%
See 1 more Smart Citation
“…The result was in agreement with the finding of Wibowo et al, (2021) they mentioned that the difference in tuber color is caused by differences in the carotene pigment content in each variety.…”
Section: Both Of Inside and Outside Color Index Potato Tuberssupporting
confidence: 92%
“…Regarding the rolling resistance of the tubers, it can be found that commonly for two varieties in the first two classes, this property was the highest and lowest on the galvanized iron sheet and the rubber and the wood surface, respectively. Wibowo et al, (2021), mentioned that the brightness level of Atlantic potato tuber flour produced was relatively high, ranged from 67.9 to 76.38. The higher the L-value means the brighter the color of the flour.…”
Section: Introductionmentioning
confidence: 99%
“…Kemudian, disampaikan (Wijaya et al, 2014(Wijaya et al, , 2015a(Wijaya et al, , 2015b(Wijaya et al, , 2018(Wijaya et al, , 2019a(Wijaya et al, , 2020a bahwa kombinasi pupuk organik dan beberapa jenis bio-arang, antara lain arang kayu, arang sekam, dan arang aktif, sebagai zat pembenah tanah, yang diaplikasikan pada budidaya kentang, mampu mendukung dinamika air dan nutrisi di dalam tanah secara seimbang, sehingga dapat mempertahankan ketersediaan nutrisi di dalam tanah secara berkelanjutan sampai menjelang masa panen. Hasil tersebut didukung oleh (Wibowo et al, 2014(Wibowo et al, , 2021 yang menyatakan bahwa aplikasi pupuk oraganik dan bio-arang berkontribusi terhadap kualitas umbi kentang.…”
Section: Pendahuluanunclassified
“…These lateral roots usually originate from the pericycle and grow through the cortex of the parent root. Once the lateral root breaks through the outer epidermal layer to the outside, pathogens create an entrance by the resulting crevice (Huang 1986;Gudesblat et al 2009;Meeteren and Aliniaeifard 2016;Vanhoutte et al 2016;Carvalho et al 2017;Silva et al 2018;Wibowo et al 2021). The space created by lateral-root formation is a representative avenue of entry for pathogens.…”
Section: Injuries and Wound Structuresmentioning
confidence: 99%